'It's difficult to help when I am not sitting next to them': How COVID-19 school closures interrupted teachers' care for newly arrived migrant and refugee learners in Denmark. Issue 1 (2nd January 2021) - Primdahl, Nina Langer; Borsch, Anne Sofie; Verelst, An; Jervelund, Signe Smith; Derluyn, Ilse; Skovdal, Morten
ABSTRACT: Teachers play a critical role in providing social and emotional support for newly arrived migrant and refugee learners. Such care ordinarily takes place in the classroom, raising questions about the impact of the 2020 COVID-19 school closures on their care work. In this article we analyze qualitative data from phone interviews with eight teachers in Danish preparatory classes, paying particular attention to the challenges they faced staying in contact with, and supporting, migrant and refugee learners during the school closure. The interviews were coded and thematically analysed, revealing significant changes in the teachers' care work. We draw on the concepts of caringscapes and carescapes to unravel how the shifts in space, from physical copresence in the school classroom to distance learning, affected their care work. Despite many efforts, teachers reported difficulties staying in contact with the learners remotely due to their limited access to virtual communication platforms and language barriers. These communication difficulties and the lack of bodily copresence not only made teaching highly challenging, but interrupted their care work, including maintaining daily schedules and facilitating social closeness between learners. Furthermore, the teachers expressed concern about their inability to link and refer the most vulnerable learners to external support services, which were temporarily closed due to the societal lockdown. Our study highlights how COVID-19 induced school closures constrain the care work of teachers of migrant and refugee learners. The concerns and struggles raised in this article not only stress the importance of the physical school space and closeness in facilitating care for newly arrived migrant and refugee learners, but signal the vulnerabilities of this group of children during times of crisis.